ANALISIS EKONOMI PEMANFAATAN KAYU KELAPA DENGAN MODEL PROGRAMA DINAMIKA : Suatu Studi Kasus di Daerah Sulawesi Utara - Esry H. O H. O Laoh; B D Nasendi (Jurnal Penelitian Hasil Hutan, 1996)
Coconut  wood  has  been potentially   available  as  a  source  of  raw  material for wood processing  industries for  many years.  Coconut  wood is a non-traditional  forestry  timber. In  forestry jargon  coconut  wood  is classified as a non-wood or non-timber product.  As a source of industrial  raw  material for boards  and planks  and for  fumiture  components  and  housing utensils plenty  of coconut   woods are available as wood substitutes  throughout Indonesia. It is technically  as  well  as  economically  viable.   Its  investment  opportunities   is  good  and  its prospects is also promising.The analysis was based on a case study which was conducted in North Sulawesi Province of eastern  Indonesia   using   a   dynamic  programming   aproach   to  identify   and   to   analyse intertemporal investment allocation possibilities  and its best altematives  to gain financial  and economic  return.   When the limited funds were to be best dicided and allocated based on scarcityresource allocation  decision approach then the dynamic programming  model has proven  as a best choice.  Eventhougk  the model is not a best one but it is available  to guide the decision makers to best posible alternative solutions in a decision making process.Keywords :   Dynamic  Progranuning  Model,   Coconut   Wood  utilization,  North  Sulawesi.